Coordinated target tracking by multiple unmanned surface vehicles with communication delays based on a distributed event-triggered extended state observer. (1st May 2021) - Gao, Shengnan; Peng, Zhouhua; Liu, Lu; Wang, Haoliang; Wang, Dan
Abstract: This paper is concerned with a coordinated target tracking problem for a network of unmanned surface vehicles (USVs) subject to communication delays and constrained actuation resources. The target to be tracked maneuvers with arbitrary velocity. Its position can be measured by a small fraction of USVs whereas its velocity is not known to follower USVs. A resource-aware event-triggered control design method is presented for coordinated target tracking. Specifically, a distributed event-triggered extended state observer (ESO) is designed to estimate the position and velocity of the target over a cooperative estimation network. Furthermore, the above result is extended to cooperative estimation subject to communication delays, and a time-delayed distributed event-triggered ESO is designed. In the control law design, an event-triggered anti-disturbance position tracking control law is proposed for each follower USV based on a reduced-order ESO. By the proposed resource-aware event-triggered control laws, cooperative target tracking can be achieved regardless of the model uncertainty and external disturbances. Moreover, both the execution rate of the actuators and communication burden of the network are reduced. The stability of the closed-loop system is proven through input-to-state stability and cascade stability analysis. Simulation results demonstrate the effectiveness of the proposed method for the coordinated target tracking of USVs. Highlights: A resource-aware control design method is proposed for achieving coordinated target tracking. A time-delayed distributed event-triggered ESO is designed to estimate the position and velocity of the target. The event-triggered position tracking control law is proposed for each follower USV based on a reduced-order ESO. The distributed event-triggered ESO is the first trial to address the cooperative target tracking problem of multiple USVs.